IMPLEMENTATION OF STAD LEARNING MODELS TO IMPROVE 5th STUDENTS’ CRITICAL THINKING SKILLS AND MATHEMATICS LEARNING OUTCOMES - Gustia, Diah Edwin; Mawardi, Mawardi; Astuti, Suhandi (Jurnal Daya Matematis, 2018)
This study is aims to improve critical thinking skills and mathematics learning outcomes of 5th grade students using the STAD (Students Team Achievement Division) instructional model. This research used was Classroom Action Research, with two cycles. The subjects of this study is 31 fifth grade students of SDN Tingkir Lor Salatiga. The instrument used was the critical thinking questionnaire and 15 items test. The results showed that the STAD instructional model can improve critical thinking skills and student learning outcomes. Improved of critical thinking skills can be seen from the average score in cycle I of 58, in the sufficient category, then increased to 77 in the high category in cycle II. Improved of learning outcomes can be seen from the acquisition of scores in the first cycle of 66, with a percentage of learning completeness of 61%, increasing to 80, with the percentage of learning completeness reaching 84% ini cycle II